Screening current rotation effects: SCIF and strain in REBCO magnets. (5th August 2021) - Kolb-Bond, D; Bird, M; Dixon, I R; Painter, T; Lu, J; Kim, K L; Kim, K M; Walsh, R; Grilli, F
Abstract: Screening currents and their effect on the magnetic field and strain state have been shown to be a major problem in the design and operation of rare-earth-barium-copper-oxide magnets, distorting the field and rotating the conductor to potentially large strains. The latter is a possible catalyst for damage as both plastic deformation and degradation of the critical current leading to reduced fatigue life or even catostrophic failure. Due to the nonlinear dynamic behavior of the screening currents and the significant possible rotation, including this rotational effect in the electromagnetic state requires a new addition to the existing models. The effect of the changing rotation angle of the conductor on the electromagnetic and stress state is investigated by using a modified homogeneous T–A method. Numerical results are compared with experimental tests.